Developing Context-Based Teaching Competencies of Chemistry Teachers: Designing and Implementing Context-Based Activities - Mustafaoğlu, Fatma Merve; Yücel, Ayşem Seda (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2022)
Context-based teaching is the use of contexts as a starting point for the development of scientific ideas in learning environments. Teachers can use this teaching approach to increase students' motivation and willingness to learn science. The focus of this research was to develop context-based teaching competencies of teachers. With this in mind, this research aimed to determine the effects of feedback on the development of teachers' context-based teaching competency and the factors affecting the teaching process. In the study, collective case study design was employed. The study was carried out with two chemistry teachers who participated in the In-Service Training Course on Context-Based Chemistry Teaching conducted by the researcher. The data of the research were collected through field notes, semi-structured interview, follow up interviews and video recordings. As a result of the research, it was determined that the feedback had a positive effect on the development of chemistry teachers' context-based teaching competency. It was revealed that teacher anxiety, professional knowledge, difficulty in designing materials and lack of interest of students affected the teaching process.